DINAROMYS BOGDANOVI (MAMMALIA: RODENTIA) FROM THE MIDDLE PLEISTOCENE OF WESTERN LOMBARDY (ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
The finding of Dinaromys bogdanovi of Middle Pleistocene age in the area of Campo dei Fiori (Varese) is described. It extends westward the distribution of this species, known previously up to eastern Lombardy only.
Keywords: Dinaromys; Rodentia; Mammalia; Middle Pleistocene; Cave; Campo dei Fiori (Varese).